Induced spawning of a river catfish Hemibagrus nemurus (Valenciennes, 1840) - Adebiyi, Fatimat Adenike; Siraj, Siti Shapor; Harmin, Sharr Azni; Christianus, Annie (Universiti Putra Malaysia Press, 2013)
There is a developing interest in Hemibagrus nemurus culture. Most hatcheries depend on fry from the wild, which is under threat due to human activities. Hatchery production of H. nemurus is not well established due to problems associated with artificial propagation. Good egg quality is essential for fry production. This paper reports the findings of research conducted to determine the effects of mammalian gonadotropin releasing hormone analogue (GnRHa) and ovaprim on induced spawning performance and egg quality of H. nemurus. Mature female H. nemurus were treated with 0.5ml of 0.7% NaCl (control), 5µg/kg, 20µg/ kg, 50µg/kg body weight (BW) of fish GnRHa and 0.5ml/kg BW of fish of ovaprim (20µg/ ml sGnRHa and 10mg/ml domperidone). The results showed that the administration of 5µg/ kg BW GnRHa is not sufficient to induce the spawning of H. nemurus. The egg quality of fish treated with GnRHa at doses 20µg/kg and 50µg/kg were numerically different, however, there was no significant difference (P>0.05). Ovaprim treated fish produced the best results. Ovulatory response ranged from 50.0% to 66.7% among all the treatments with high fertilization rate (94-95%). The highest hatching rate (78.3%) and percentage of normal larvae (68.8%) was observed from ovaprim injected fish. The results indicated that 20µg/kg and 50µg/kg BW GnRHa were effective in inducing ovulation and spawning in H. nemurus and ovaprim can be recommended to be used by hatcheries to induce H. nemurus for spawning. The major significance of this work was 5µg/kg dose of GnRHa is ineffective for ovulation in H. nemurus.